2020
DOI: 10.1101/2020.03.07.981951
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Plasmodiumoocysts respond with dormancy to crowding and nutritional stress

Abstract: 11Malaria parasites develop and grow as oocysts in the mosquito for several days before being able to 12 infect another human. During this time, mosquitoes take regular bloodmeals to replenish their 13 nutrient and energy reserves needed for flight and reproduction. We hypothesized that supplemental 14 bloodmeals are critical for oocyst growth and that experimental infection protocols, typically 15 involving a single bloodmeal, cause nutritional stress to developing oocysts. Therefore, 16 enumerating oocysts i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 39 publications
3
18
1
Order By: Relevance
“…Here, we demonstrate that multiple blood feedings significantly accelerate parasite growth, shortening the time required for sporozoites to appear in the salivary glands. These findings are consistent with infection studies in closely related mosquito species that showed that an additional blood meal during development either boosts P. falciparum sporozoite intensities(21,22,31) or increases oocyst size (20-22), although none analyzed parasite growth rates after the second meal. Our study conclusively links the effects of an additional blood meal to increased parasite developmental rates and a shortened EIP.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…Here, we demonstrate that multiple blood feedings significantly accelerate parasite growth, shortening the time required for sporozoites to appear in the salivary glands. These findings are consistent with infection studies in closely related mosquito species that showed that an additional blood meal during development either boosts P. falciparum sporozoite intensities(21,22,31) or increases oocyst size (20-22), although none analyzed parasite growth rates after the second meal. Our study conclusively links the effects of an additional blood meal to increased parasite developmental rates and a shortened EIP.…”
supporting
confidence: 88%
“…Moreover, multiple feeds may be required even within a single reproductive cycle due to interrupted feeding or to nutrient deprivation during the larval stage (pre-gravid behavior) (19). Additional blood meals may therefore potentially influence oocyst growth and the EIP, as suggested by reports showing an additional feed can increase P. falciparum oocyst size (20, 21) and salivary gland sporozoite numbers at a given time point (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…Here, we demonstrate that multiple blood feedings significantly accelerate parasite growth, shortening the time required for sporozoites to appear in the salivary glands. These findings are consistent with infection studies in closely related mosquito species that showed that an additional blood meal during development either boosts P. falciparum sporozoite intensities or yields [22][23][24][25][26]34] or increases oocyst size [21][22][23], although none analyzed parasite growth rates after the second meal. Our study conclusively links the effects of an additional blood meal to increased parasite developmental rates and a shortened EIP.…”
Section: Plos Pathogenssupporting
confidence: 88%
“…Current estimates indicate climate change has the potential to change the number of people at risk of malaria (56,60,61), though there is uncertainty due to the complexity of how the parasite and given that our model assumes the EIP is determined on a per-oocyst basis and that developmental times are independent within an individual mosquito which needs to be verified experimentally. What's more, other processes may be operating: emerging experimental evidence hints that a decrease in resource availability per parasite (at high parasite loads), as determined by the parasite load and the number of times the mosquito blood-feeds, may decrease the parasite development rate (48,67). Since (a) transmission is highly sensitive to changes in EIP, (b) transmission blocking interventions cause a decline in oocyst intensity (38), and (c) parasite load in the field may be higher than previously thought (37), the influence of parasite load on EIP merits further investigation.…”
Section: Discussionmentioning
confidence: 99%